Reservoir heterogeneity in deep marine-continental transitional shales: the role of lithofacies and quality in the coal-bearing longtan formation, central Sichuan basin - Wang, Longyi; Li, Xizhe; Chen, Ya’na; Zhan, Hongming; Pei, Xiangyang; Chen, Yuchuan; Qi, Nijun; He, Weikang; Yu, Wenxuan; Lin, Yaoqiang; Zhou, Yuhang (Frontiers in Earth Science, 2025)
Compared with marine shale formations, marine-terrestrial transitional shales exhibit rapid lithofacies changes. This poses significant challenges for the classification of shale lithofacies and the study of their characteristics. The Permian Longtan Formation (LTF) coal-measure shale in marine-terrestrial transitional facies in the central-southern Sichuan Basin is expected to be a new gas-rich formation with development value in China. Based on core observation and thin-section identification, and using techniques such as XRD, TOC analysis, field-emission scanning electron microscopy, low-temperature gas adsorption, and high-pressure mercury intrusion, this study systematically analyzed the lithofacies types, geochemical characteristics, and pore features of the LTF coal-measure shale in the deep area (4,220–4,400 m) of the central Sichuan Basin. The study shows that the shale in the studied interval mainly developed four lithofacies: organic-rich clay shale (CS-H), medium-organic mixed shale (MS-M), medium-organic siliceous shale, and low-organic calcareous shale (CAS-L). The four lithofacies are interbedded with each other, and their characteristics differ significantly. Clay content and TOC content are the main factors affecting their quality. Through multiparameter analysis, it is determined that the CS-H lithofacies has a good hydrocarbon generation basis, well-developed pores, and good preservation conditions, making it a high-quality lithofacies. The research conclusions provide important insights into the study of marine-terrestrial transitional shale formations and offer a basis for further advancing the development and utilization of transitional shales.